The Value of “Tha Non Kon Dern” Walking Street as a Space to Enhance Tourism in Nakhon Phanom Province - Kewsri, Supratra; Chunhabunyatip, Prompsssorn; Buathong, Kantapop (International Journal of Multidisciplinary in Management and Tourism, 2022)
Walking street has become a part of the social value for locals and tourists. The image of the walking street will be changed as the space becomes more modernized to attract tourists. This article aims to study (1) the physical of the walking Street setting for the zone (2) to assess the existing qualities of the walking Street as a social space for tourists. On the characteristics of tourists, data was obtained from 400 randomly selected respondents. Content analysis and descriptive statistics are used to analyze data. The following are the findings of the study: 1. The Walking Street is located on Main Street in the heart of the city, beside the Maekhong River. From Friday to Saturday, from 5.00 p.m. to 10.00 p.m., a traditional market selling a variety of home things is held. The setting up of tents by the merchants who normally sell garments and accessories on the street from evening to late at night was spotted on the south areas of the street. Five zones were created in the walking street area. 2. In terms of physical setting and landscape setting, the tourists agreed that the "Tha Non Kon Dern" Walking Street provided a wonderful experience. There appears to be a clear link between the physical setting and the landscape setting, with the site context area supporting the majority of leisure or social activities. The Walking Street itself is located by Mekhong River, which is surrounded by an old buldging historical site. Instead of only having social interaction between sellers and tourists, the Walking Street creates locations for tourists to sit and pause, allowing people to socialize, watch and listen to other people, or enjoy the sight, sound, and scent.